A High-Throughput Hardware Architecture for the H.264/AVC Half-Pixel Motion Estimation Targeting High-Definition Videos. (28th October 2010) - Corrêa, Marcel M.; Schoenknecht, Mateus T.; Dornelles, Robson S.; Agostini, Luciano V.
Abstract : This paper presents a high-performance hardware architecture for the H.264/AVC Half-Pixel Motion Estimation that targets high-definition videos. This design can process very high-definition videos like QHDTV (3840 × 2048 ) in real time (30 frames per second). It also presents an optimized arrangement of interpolated samples, which is the main key to achieve an efficient search. The interpolation process is interleaved with the SAD calculation and comparison, allowing the high throughput. The architecture was fully described in VHDL, synthesized for two different Xilinx FPGA devices, and it achieved very good results when compared to related works.